The Effect of Intracavernosal Injection of Stem Cell in the Treatment of Erectile Dysfunction in Diabetic Patients: A Randomized Single-blinded Clinical Trial: Stem cell therapy for erectile dysfunction - Mirzaei, Mahboubeh; Bagherinasabsarab, Mohammadali; Pakmanesh, Hamid; Mohammadi, Reza; Teimourian, Mohammad; Jahani, Yunes; Farsinejad, Alireza (Urology Journal, 2021)
Purpose: The prevalence of erectile dysfunction in men is increasing. As well, the prevalence of diabetes, as one of the causes of sexual dysfunction, is rising in many countries. Due to the failure of common therapies in some patients with sexual dysfunction, it is necessary to develop an effective alternative treatment, such as stem cell therapy, for this problem. Materials and Methods: In this randomized single-blinded clinical trial, 20 diabetic patients with erectile dysfunction, who were resistant to common treatments, were selected and divided into two groups of intervention and control (n=10 per group). Autologous mesenchymal stem cells (MSCs) were extracted from oral mucosa and then infused via intracavernosal injection (50-60 ×106 cells) to the participants of the intervention group. Normal saline was injected in the control group. The patients were followed up with the International Index of Erectile Function (IIEF5) questionnaire, as well as color Doppler duplex ultrasound. Peak systolic velocity (PSV), end diastolic velocity (EDV), and resistance index (RI) were determined three and six months after the interventions. Results: The mean IIEF5 scores in the intervention group were 7.2 ± 2.1, 9.2 ± 3.4, and 10.6 ± 4.7 before, three months, and six months after the injection, respectively, showing a significant ascending trend (P = 0.01). Comparing the intervention and control groups, there was a significant difference in the IIEF5 score change during six months after the injection (P = 0.02). Regarding the PSV and RI of penis vessels, there were no statistically significant differences between the two groups. However, these parameters showed upward and improving trends in the intervention group. Conclusion: Intracavernosal injection of stem cells improved sexual function and PSV and RI indices of penile arteries in diabetic patients.